2022
DOI: 10.1016/j.meegid.2021.105195
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into sex-specific non-coding RNAs and networks in response to SARS-CoV-2

Abstract: SARS-CoV-2 is the RNA virus responsible for COVID-19, the prognosis of which has been found to be slightly worse in men. The present study aimed to analyze the expression of different mRNAs and their regulatory molecules (miRNAs and lncRNAs) to consider the potential existence of sex-specific expression patterns and COVID-19 susceptibility using bioinformatics analysis. The binding sites of all human mature miRNA sequences on the SARS-CoV-2 genome nucleotide sequence were predicted by the miRanda tool. Sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Apart from histone modifications and DNA methylation, non-coding RNA (nc-RNA) is an important contributor of epigenetic changes. In COVID-19, several nc-RNA are upregulated or downregulated which render them as potential biomarkers of the disease [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Askari et al reported that several long nc-RNAs and micro RNAs (mi-RNAs) are differentially expressed in COVID-19, some with specific observations in female versus male patients [ 46 ].…”
Section: Altered Epigenomic Signature Of Dna Methylation In Heart Imp...mentioning
confidence: 99%
See 4 more Smart Citations
“…Apart from histone modifications and DNA methylation, non-coding RNA (nc-RNA) is an important contributor of epigenetic changes. In COVID-19, several nc-RNA are upregulated or downregulated which render them as potential biomarkers of the disease [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Askari et al reported that several long nc-RNAs and micro RNAs (mi-RNAs) are differentially expressed in COVID-19, some with specific observations in female versus male patients [ 46 ].…”
Section: Altered Epigenomic Signature Of Dna Methylation In Heart Imp...mentioning
confidence: 99%
“…In COVID-19, several nc-RNA are upregulated or downregulated which render them as potential biomarkers of the disease [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Askari et al reported that several long nc-RNAs and micro RNAs (mi-RNAs) are differentially expressed in COVID-19, some with specific observations in female versus male patients [ 46 ]. For example, comparison of female versus male COVID-19 ICU patients showed upregulation in XIST lncRNA, while downregulation in TTTY14 , TTTY10 , and ZFY-AS1 lncRNAs [ 46 ].…”
Section: Altered Epigenomic Signature Of Dna Methylation In Heart Imp...mentioning
confidence: 99%
See 3 more Smart Citations